2016
DOI: 10.1080/14689367.2016.1184623
|View full text |Cite
|
Sign up to set email alerts
|

Overload breakdown in models for photosynthesis

Abstract: In many models of the Calvin cycle of photosynthesis it is observed that there are solutions where concentrations of key substances belonging to the cycle tend to zero at late times, a phenomenon known as overload breakdown. In this paper we prove theorems about the existence and non-existence of solutions of this type and obtain information on which concentrations tend to zero when overload breakdown occurs. As a starting point we take a model of Pettersson and Ryde-Pettersson which seems to be prone to overl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…Poolman suggested that overload breakdown could be avoided by introducing the release of G1P from starch. In the case of Model 3.2.1 it was shown in [12] that if k 3 c A ≤ 5k 28 there exists a Lyapunov function related to the function L 1 of the last section and this proves that under this condition Model 3.2.1 has no positive steady states. Here the k i are reaction constants and c A is the total concentration of adenosine phosphates.…”
Section: The Pettersson Model and Modifications Of Itmentioning
confidence: 82%
See 2 more Smart Citations
“…Poolman suggested that overload breakdown could be avoided by introducing the release of G1P from starch. In the case of Model 3.2.1 it was shown in [12] that if k 3 c A ≤ 5k 28 there exists a Lyapunov function related to the function L 1 of the last section and this proves that under this condition Model 3.2.1 has no positive steady states. Here the k i are reaction constants and c A is the total concentration of adenosine phosphates.…”
Section: The Pettersson Model and Modifications Of Itmentioning
confidence: 82%
“…In [6] and [17] the inequality relating k 2 and k 6 was not given any biological interpretation and no explanation was given for the Lyapunov function which was found by trial and error. More insight on these questions was obtained while studying a more complicated model of the Calvin cycle in [12]. The reaction constant k 6 controls the rate of export of PGA from the chloroplast and in reality this is coupled to the import of inorganic phosphate.…”
Section: The Five-species Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…This kind of behaviour can be ruled out if the model admits a suitable conservation law. This is, for instance, the case in a model of [16] whose mathematical properties were studied in [13]. In the model of Hahn with photorespiration boundedness of solutions is obtained without there being a conservation law.…”
Section: Discussionmentioning
confidence: 99%
“…This means intuitively that the production of sugar by the cycle cannot meet the demand for export from the chloroplast. In [13] it was shown that there are solutions of the model of [16] which admit this phenomenon while in a modification of the model due to Poolman [17] these solutions are eliminated. The model of [17] does not include photorespiration but does include the mobilization of glucose from starch.…”
Section: Discussionmentioning
confidence: 99%